Entrenchment and Alignment Effect on Earnings Management - Yanti Puji Astutie; Anis Chariri; Siti Mutmainah (The Indonesian Journal of Accounting Research, 2013)
The objective of this research is to investigate whether controlling shareholders manages earnings. A weak protection for noncontrolling shareholders (Johnson et. al., 2000a) coupled with concentrated ownership for majority of public companies in Indonesia, provides incentive to the controlling shareholders to manage earnings. In particular, this study investigates whether controlling shareholders entrench by managing earnings upwards as their control rights becomes greater than their cash flow rights and aligns by managing earnings downwards as their cash flow rights approaches to their control rights. I use ultimate ownership and financial statement data collected from companies listed in Indonesia Stock Exchange (IDX) from 2001 to 2007. I find, for 786 firm year observations, that firms controlled by ultimate shareholders with greater control rights are associated with higher level of discretionary accruals. Consistent with entrenchment hypothesis, the results suggest that ultimate shareholders use their greater control rights to influence controlled firms to manage earnings. On the other hand, I also find that consistent with entrenchment hypothesis, as cash flow rights of the ultimate shareholders increases, the level of discretionary accruals of the controlled firms tends to decrease.